Penguatan Pendidikan Karakter Melalui Kegiatan Pembiasaan Senam Pagi Sebelum Pembelajaran di SDN 4 Wagir Lor. - Muhammad Syauqi Sulthoni; Haniatul Mukaromah (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This article discusses the strengthening of character education through morning exercise habituation activities before learning at SDN 4 Wagir Lor. Morning exercise is not only a physical activity to maintain health and fitness, but also a medium for shaping students’ character, particularly in terms of discipline, responsibility, cooperation, togetherness, and health awareness. This study employed the ABCD (Audience, Behavior, Condition, Degree) approach with all students of SDN 4 Wagir Lor as the research subjects. The findings indicate that routine morning exercise significantly improves students’ punctuality, enhances their learning motivation, fosters a sense of togetherness, and helps internalize character values into their daily lives. Therefore, morning exercise is proven to be a simple yet effective strategy to strengthen character education while simultaneously improving the quality of learning in elementary schools.